The Study of Low-Level Authentication Mechanism Based on Physical Layer Characteristics - Chen, Kai; Chen, Longru; Lu, Jianxian; Dai, Gaoyuan; Wang, Zhe; Yu, Liyang (2023 International Conference on Networks, Communications and Intelligent Computing (NCIC), 2023)
The advent of 5G networks brings about a monumental transformation. It is characterized by significantly larger bandwidth, lower latency transmission, and diverse connectivity of multi-type terminal devices. This paradigm shift in mobile communication technology introduces new challenges in network security. This paper introduces an authentication mechanism based on the physical layer attributes, leveraging Physical Unclonable Functions (PUFs) to address authentication and privacy protection for resource-constrained devices. The application of physical layer security techniques involves embedding authentication information within wireless communication signals. This augmentation enhances system security. However, challenges, including integration with novel transmission technologies, implementing secure transmission mechanisms across diverse network scenarios, and addressing emerging security threats, must be overcome. PUFs, known for their persistence, unclonability, and tamper-evident properties, have versatile applications across various domains. This study emphasizes the requirements of PUFs in 5G networks. It encompasses research areas such as secure key generation based on PUFs and key negotiation mechanisms rooted in wireless channel characteristics. These efforts aim to address specific scenarios and emerging security threats.